Colonic Spirochetosis in a 60-Year-Old Immunocompetent Patient: Case Report and Review. (3rd August 2016) - Ngwa, Taiwo; Peng, Jennifer L.; Choi, Euna; Tayarachakul, Sucharat; Liangpunsakul, Suthat
Spirochetes, a genetically and morphologically distinct group of bacteria, are thin, spiral-shaped, and highly motile. They are known causes of several human diseases such as syphilis, Lyme disease, relapsing fever, and leptospirosis. We report a case of colonic spirochetosis in a healthy patient presenting for surveillance colonoscopy. The diagnosis of intestinal spirochetosis was made accidentally during the histological examination of colonic polyps, which were removed during colonoscopy. We also performed an extensive review on intestinal spirochetosis with a focus on clinical presentation and outcomes of reported cases from the past two decades.